Experiences of Oral Corticosteroid Use and Adverse Effects: A National Cross-Sectional Survey of People with Asthma - Jones AW; McDonald VM; McLoughlin RF; Vella TM; Flynn AW; Blakey JD; Wolfenden L; Hew M; Upham JW; Thomas D; Bardin P; Holland AE (Patient Preference and Adherence)
Arwel W Jones,1 Vanessa M McDonald,2– 5 Rebecca F McLoughlin,2– 4 Teresa M Vella,6 Anthony W Flynn,7 John D Blakey,8,9 Luke Wolfenden,10,11 Mark Hew,12 John W Upham,13,14 Dennis Thomas,2,4 Philip Bardin,15 Anne E Holland1,2,16 1Respiratory Research@Alfred, Monash University, Melbourne, VIC, Australia; 2Centre of Excellence in Treatable Traits, University of Newcastle, Newcastle, NSW, Australia; 3School of Nursing and Midwifery, University of Newcastle, Newcastle, NSW, Australia; 4Hunter Medical Research Institute Asthma and Breathing Program, Newcastle, NSW, Australia; 5Department of Respiratory and Sleep Medicine, John Hunter Hospital, Newcastle, NSW, Australia; 6Brand and Engagement, Asthma Australia, Brisbane, QLD, Australia; 7Research, Information and Evaluation, Asthma Australia, Melbourne, VIC, Australia; 8Respiratory Medicine, Sir Charles Gairdner Hospital, Perth, WA, Australia; 9Medical School, Curtin University, Perth, WA, Australia; 10Hunter New England Population Health, Wallsend, NSW, Australia; 11School of Medicine and Public Health, University of Newcastle, Callaghan, NSW, Australia; 12Allergy, Asthma & Clinical Immunology, Alfred Health, Melbourne, VIC, Australia; 13Frazer Institute, University of Queensland, Brisbane, QLD, Australia; 14Department of Respiratory Medicine, Princess Alexandra Hospital, Brisbane, QLD, Australia; 15Monash Lung Sleep Allergy & Immunology, Monash University and Medical Centre, Clayton, VIC, Australia; 16Physiotherapy Department, Alfred Health, Melbourne, VIC, AustraliaCorrespondence: Arwel W Jones, Respiratory Research@Alfred, School of Translational Medicine, Monash University, Alfred Centre, Melbourne, VIC, 3004, Australia, Email arwel.jones@monash.eduPurpose: Oral corticosteroids (OCS) are an effective treatment for severe uncontrolled asthma or asthma exacerbations, but frequent bursts or long-term use carry serious and sometimes irreversible adverse effects, or complications such as adrenal insufficiency upon discontinuation. Our aim was to survey people with asthma on their experiences of, and attitudes towards, using OCS.Patients and Methods: This study was a national descriptive cross-sectional survey of people with asthma in Australia. An anonymous survey was hosted online with invitations to participate distributed by national consumer peak bodies. Survey free-text responses were coded to the Theoretical Domains Framework (TDF) to elicit determinants of OCS use.Results: 1808 people with asthma participated between 3 and 16 May 2022. Most common reasons for using OCS were severe asthma symptoms (40%), doctor prescription (38%) or asthma action plan recommendations (20%). Approximately 55% of people had experienced adverse effects from OCS use. Commonly reported adverse effects were trouble sleeping (69%), weight gain (56%) and mood problems (41%). Of people who had OCS at home or an OCS script, 44% did not have an action plan that described when and how they should take them. People (33%) did not feel well informed about OCS adverse effects from their healthcare team. People had varied awareness (3– 65%) of current available strategies to reduce OCS use. ‘Knowledge’, ‘Environmental context and resources’ and ‘Social influences’ were the most coded TDF domains influencing OCS use.Conclusion: Adverse effects of OCS use are common. People with asthma are not adequately informed about optimal OCS use or strategies to reduce overuse. These findings can help guide the implementation of OCS stewardship initiatives.Keywords: asthma, corticosteroids, consumer behaviour, attitude, patient participation